2022
DOI: 10.3892/etm.2022.11226
|View full text |Cite
|
Sign up to set email alerts
|

Second endoscopic retrograde cholangiopancreatography after failure of initial biliary cannulation: A single institution retrospective experience

Abstract: Endoscopic retrograde cholangiopancreatography (ERCP) is not always successful when difficult biliary cannulation occurs. A second ERCP seems to be a worthwhile option following initial failure cannulation; however, relevant data are limited. Thus, the aim of the present study was to determine the outcomes of repeating ERCP in patients in whom the first biliary cannulation with or without precut sphincterotomy failed. It retrospectively analyzed 4,136 patients who underwent an initial biliary access between Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…The majority of pancreaticobiliary disorders are now diagnosed and treated with ERCP, which is a minimally invasive procedure. Studies have shown that experienced endoscopists using a needle-knife have improved the cannulation success rate to between 85% and 99%; however, the matter of selecting the best substitute among the available options in the event of initial ERCP failure still holds interest [1,11]. A subsequent ERCP within a few days is an effective and safe therapy for patients who are clinically stable, with a success rate of 68%-79% [2,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of pancreaticobiliary disorders are now diagnosed and treated with ERCP, which is a minimally invasive procedure. Studies have shown that experienced endoscopists using a needle-knife have improved the cannulation success rate to between 85% and 99%; however, the matter of selecting the best substitute among the available options in the event of initial ERCP failure still holds interest [1,11]. A subsequent ERCP within a few days is an effective and safe therapy for patients who are clinically stable, with a success rate of 68%-79% [2,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic retrograde cholangiopancreatography (ERCP) is a minimally invasive intervention that has established itself as the gold standard therapeutic option for various pancreaticobiliary conditions [1]. Nonetheless, there are times when ERCP is ineffective, even when performed by highly trained professionals or at major healthcare institutions [2].…”
Section: Introductionmentioning
confidence: 99%
“…According to Flumignan [ 18 ] and Deng [ 19 ], a second fistulotomy attempt is feasible, and safe, and can be attempted after a short 48-hour interval if the first ERCP attempt is unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…There must be a golden time for a second ERCP, as the perforation will progressively increase inflammation in the periampullary region. A second ERCP is defined as a safe procedure 2–4 days after failure of the first biliary cannulation [ 19 , 20 ]. Since type 2 perforations already have sphincterotomy, cannulation is not difficult in very early period.…”
Section: Discussionmentioning
confidence: 99%